Brazilian Version of the Protocole Montréal d’Évaluation de la Communication (Protocole MEC): normative and reliability data - Paz Fonseca, Rochele; Joanette, Yves; Côté, Hélène; Ska, Bernadette; Giroux, Francine; Guimarães Fachel, Jandyra Maria; Damasceno, Gabriela; Mattos Pimenta Parente, Maria Alice De (The Spanish Journal of Psychology, 2008)
The lack of standardized instruments to evaluate communication disorders related to the right hemisphere was verified.A new evaluation tool was developed: Protocole Montréal d’Évaluation de la Communication – Protocole MEC, adapted to Brazilian Portuguese – Bateria Montreal de Avaliação da Comunicação – Bateria MAC (Montreal Evaluation of Communication Battery). The purpose was to present stratified normative data by age and educational level, and to verify the reliability parameters of the MEC Battery. 300 individuals, between the ages of 19 and 75 years, and levels of formal education between 2 and 35 years, participated in this study. They were divided equally into six normative groups, according to three age categories (young adults, intermediary age, and seniors) and two educational levels (low and high). Two procedures were used to check reliability: Cronbach alpha and reliability between evaluators. Results were established at the 10th percentile, and an alert point per task for each normative group. Cronbach’s alpha was, in general, between .70 and .90 and the average rate of agreement between evaluators varied from .62 to .94. Standards of age and education were established. The reliability of this instrument was verified. The psychometric legitimization of the MEC Battery will contribute to the diagnostic process for communicative disorders.
Keywords: Communication evaluation; Montreal; MEC; Brazil; Psychometric properties